PERBANDINGAN PENGENAAN PBB SEKTOR PERDESAAN & PERKOTAAN DI PROVINSI DKI JAKARTA , BEKASI, & DEPOK BERDASARKAN SPPT PBB TAHUN 2014 & 2015 - Fitria Arianty; Thesa A. Purwanto (Jurnal Vokasi Indonesia, 2015)
AbstractTax on Land and Building, Rural and Urban Sector based on the regional regulation may vary fromone region to another. This is because the imposition authority of tax on land and building, rural andurban sectors were handed over to local governments. This study aimed to compare the land andbuilding, Rural and Urban Sector tax policies in DKI Jakarta, Bekasi, Depok, based on SPPT 2014and 2015. In analyzing the problems of the imposition tax on land and building, rural and urbansectors in DKI Jakarta, Bekasi, Depok, information obtained from interviews with tax authorities andfield observations. The land and building, Rural and Urban Sector tax policies in DKI Jakarta, Bekasi,Depok different in terms of tax rates, determination the amount of NJOPTKP, as well as the amountof NJOP. The amount of NJOP in Jakarta is higher and more diverse than the amount of NJOP inDepok and Bekasi. Determination the amount of NJOP in Jakarta also set more frequently, whichevery year than in the city of Depok and Bekasi. This is because the value of land and buildings inJakarta faster rise than in Depok and Bekasi.Keywords: Tax on Land and Building, Rural and Urban Sector, Local Tax.